2010
DOI: 10.1155/2010/363679
|View full text |Cite
|
Sign up to set email alerts
|

Registry Evaluation of Digital Ulcers in Systemic Sclerosis

Abstract: Digital ulcers are a very frequent complication of systemic sclerosis affecting about half of the SSc patients, and about 75% of the affected patients have their first DU episode within 5 years from their first non-Raynaud symptom. The lack of adequate classification criteria as well as the lack of knowledge of the development of DU have contributed to the opening of specific registries to better understand the natural history of these lesions. For these reason, specific disease registries play a fundamental r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…In the interest of having uniform patient populations and increasing the probability of obtaining a clear answer, strong consideration should be given to disease duration [8], to the time from onset of the first DU [9] and the capillaroscopic pattern (early, active or late) [40]. In a trial studying DUs, capillaroscopic patterns can be studied as a substudy, but a limitation in using capillaroscopy is the fact that patterns are unlikely to change over a short trial.…”
Section: Inclusion Criteriamentioning
confidence: 99%
“…In the interest of having uniform patient populations and increasing the probability of obtaining a clear answer, strong consideration should be given to disease duration [8], to the time from onset of the first DU [9] and the capillaroscopic pattern (early, active or late) [40]. In a trial studying DUs, capillaroscopic patterns can be studied as a substudy, but a limitation in using capillaroscopy is the fact that patterns are unlikely to change over a short trial.…”
Section: Inclusion Criteriamentioning
confidence: 99%
“…This significance was predominately contributed by the development of higher rates of 30-day postoperative surgical site infection, urinary tract infection, bloodstream infection or sepsis when compared to controls. SSc patients with skin ulcers secondary to microcirculatory vasculopathy have been perceived to have higher rates of impaired wound healing [26][27][28] . Secondly, all-cause mortality studies in SSc populations have observed that 33% of deaths due to non-SSc-related causes were attributed to infections, particularly septicemia and pneumonia 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Documented postoperative wound infections occurred in 3.8% of procedures in our SSc cohort, comparable to the 2-5% incidence for the general surgical population and we did not observe a difference between lSSc and dSSc 28,29 . This distinction is important, since dSSc patients with skin ulcers secondary to microcirculatory vasculopathy have been perceived to have higher rates of impaired wound healing [30][31][32] .…”
Section: Discussionmentioning
confidence: 99%